Optical Conduct of Nanostructure Co3O4 rich Highly Doping Co3O4: Zn Alloys - Sami Salman Chiad (Journal of Global Pharma Technology, 2016)
The spray pyrolysis technique (SPT) was used because it is simple, low cost and less equipment. Structural, morphological and optical properties of pure Co3O4 and doping 1% and 3% Zn: Co3O4 were anayzed by X- Ray diffraction (XRD), Atomic force Microscope (AFM) and UV-visible Spectroscopy. XRD indicate a polycrystalline structure with AFM images shows that the films was discontinuous surface with spherically grains increase from (70 to 84 nm) with increase doping from 1% to 3%. The energy gap Eg was decreased from 2.75 to 1.64 eV when doping increase. Keywords: Co3O4, Zn: Co3O4 thin films, XRD, AFM and optical characterizations.